Pertimbangan Hakim Terhadap Putusan Cerai Gugat Karena Istri Selingkuh (Studi Kasus Di Pengadilan Agama Stabat No. 18/Pdt.G/2020/PA) - Ibnal Habibi (Journal Smart Law, 2025)
In essence, humans are social creatures who need other humans to navigate the wheel of life. Humansdo this by seeking friends and life partners. One way to continue their lineage is through marriage. Forhumans, marriage is not simply sexual intercourse between members of the opposite sex, as is thecase with other creatures. Rather, it aims to form a happy and lasting family. In traditional societies,marriage is even seen as a way to build, foster, and maintain harmonious and peaceful kinshiprelationships. It is a natural state of affairs that men and women, regardless of gender, are mutuallyattracted to each other and want to live together. It is well known and acknowledged that the goals ofmarriage are not always achieved according to plan, despite every effort. In fact, harmony andharmony between husband and wife can sometimes fail, leading to hostility. The causes of divorce arevaried, including interference from a third party or infidelity. Infidelity is a case of adultery andinfidelity of a husband or wife involving a third party as a lover. This thesis is included in thecategory of descriptive analytical field research, namely by conducting direct research at the StabatReligious Court which is then analyzed using deductive qualitative analysis methods. The datacollection techniques used are documentation and direct interviews with the Judges. In the analysis, a juridical and normative approach was used, so that it was known whether or not the considerations ofthe Stabat Religious Court Judge in deciding on a divorce due to infidelity were in accordance withPositive Law and Islamic Law. Therefore, based on the above facts, the Stabat Religious Court Judgeattributed infidelity as a reason for divorce to Article 19 letter (f) of PP No. 9 of 1975 JO. Article 16letter (f) Complications of Islamic Law.